PENGEMBANGAN CERITA BERGAMBAR BAHASA KRAMA PADA PEMBELAJARAN BAHASA JAWA KELAS 2 SDN MAGERSARI SIDOARJO - Kasimah; Rufi’i; Muhyi Muhammad (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
The development of Krama pictorial stories in learning Javanese 2nd grade SDN Magersari Sidoarjo requires a learning media that can support changes in students' interest in using Javanese, especially in the use of Krama Language. The purpose of this study is to determine the development of picture story books can improve language skills (speaking) and write in Javanese krama.This development design model uses the Research and Development R&D method which consists of ten steps. Among others: identification of the problem, collecting data, product design, design validation, design revisions, product trial, product revisions, trial use, product revisions and mass production.The results obtained when conducting design validation and content validation tests, as well as media attractiveness tests by students. From the learning design expert the average value of pictorial story media gets a percentage of 90.67%, from the content experts on Javanese picture story gets a percentage of 92%. Overall, the use of the Javanese picture story media gets a percentage of 80.8%, which means that the Javanese picture book story is interesting and effective for teaching and learning activities